Antimicrobial Properties of Eco Enzyme: A Literature Review - Pande Ayu Naya Kasih Permatananda; I Gde Suranaya Pandit; Putu Nita Cahyawati; Anak Agung Sri Agung Aryastuti (HM Publisher, 2023)
Background: In surgical medicine, the use of antimicrobials is very important. The use of antimicrobials or antibiotics is used at the time before surgery as prophylaxis, intraoperative, and postoperative. The prevention of some bacterial infections is imperative. The latest research is constantly evolving toward the use of antibiotics, which follows an increasingly resistant antibiotic trend. One of the advancements in the use of antimicrobials is eco enzymes. Methods: The literatures reviewed in our study was gathered from PubMed and Google Scholar. The advanced search was conducted on PubMed with the keywords used (